Culti e templi della Sicilia sud‑orientale nelle iscrizioni: Apollo e Artemide (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2012)
This contribution deals with the worship of Apollo and Artemis in Siracusa and its territory in epigraphic documents, starting from the origin of the colony up to the Hellenistic-Roman era, and also its interrelations with the veneration of other non-Greek gods worshipped in South-Eastern Sicily. The links between the cult of Apollo and that of Anna are here specifically analysed as well as those between the cult of the Paides and another oracular goddess, Maie, who was deeply venerated in Siracusa’s territory, near Akrai.  As far as Artemis is concerned, particular enphasis is put on the interpretation of an inscription relating to the cult of Artemis Pheraia in Siracusa and its connections to the two underworld goddesses Demetra and Kore, thus confirming the religious syncretism originated by the merger of different cultures.